ANALISIS PERTUMBUHAN EKONOMI DAN SEKTOR POTENSIAL: STUDI EMPIRIS DI KABUPATEN MAMUJU UTARA PERIODE 2008–2013 - Elvira, Elvira (Katalogis, 2016)
To achieve a better regional economic growth, the government should encourage the growth of sectors that have competitive advantage and take into account the development of an economic sector that is based on the ability of regional conditions or potential and available resources. This study aims at analyzing the economic growth trends, identifying the classification of potential economic sectors in sustaining economic growth during 2008-2013 and determining the elasticity of potential employment sectors. The method of this research analysis is descriptive, Typology Klassen, LQ, Shift Share, overlay, and analysis of employment elasticity. The results show (1) the economic growth of Mamuju Utara during the 2007 to 2013 has a positive direction and tends to increasing every year. (2) the classification of economic sectors is divided into three classifications, the manufacturing sector into the quadrant I which is the advanced sector and grows rapidly, agriculture, electricity, gas and water, construction, trade, hotels and restaurants, transportation and communication, finance and, leasing and business services, and the services sector go in quadrant III, potential sectors that can still be developed rapidly while entering the quadrant IV, the mining sector is relatively underdeveloped sector. (3) The manufacturing sector is a potential sector in sustaining economic growth in Mamuju Utara regency (4) the elasticity of employment opportunities in potential sectors are in agriculture and the manufacturing sector. For the agricultural sector in 2011-2012 was inelastic and 2012-2013 was elastic while the manufacturing sector in 2011-2012 and 2012-2013 is elastic.